Chemical Contributions to Neurodevelopmental Disorders. (October 2017) - Patisaul, Heather B.
Children increasingly receive diagnoses of neurodevelopmental disorders (NDDs). Causes are multifactorial, but growing consensus identifies environmental factors, especially chemical exposures, as primary drivers, with some individuals more genetically susceptible to these external pressures than others. Our current system of chemical management prioritizes rapid commercialization over disease prevention. This strategy privatizes economic benefits but socializes health costs. The evidence linking chemical exposure to neurodevelopmental risk merits greater attention by regulators. Public health concerns, particularly for children and other vulnerable groups, should be elevated in chemical risk assessment. The financial and emotional burden of preventable NDDs on U.S. children and their families calls for comprehensive policy attention.